AB0033 Systemic secreted prolactin in ra leads to proinflammatory cytokine production in macrophages. (23rd January 2014) - Tang, M. W; Reedquist, K. A.; Goffin, V.; Gerlag, D. M.; Tak, P. P.
Abstract : Background: Rheumatoid arthritis (RA) is a rheumatic disease mainly affecting women. It is known that prolactin (PRL) is a sex hormone, which apart from inducing lactation, also has immunomodulatory properties. PRL levels are elevated in the serum of both female and male RA patients compared to healthy individuals 1 . Furthermore, hyperprolactinemia is observed in 6% of patients with RA compared to 3% in the normal population 2 . It has also been observed that serum PRL levels are positively correlated with different disease parameters (eg. IgM rheumatoid factor) 3 . Limited open label clinical trials, using bromocriptine, leading to decreased PRL levels, show improvement in disease activity of RA patients 4 . Recently the prolactin receptor (PRLR), belonging to the family of cytokine receptors, has been described in synovial tissue of RA and PsA patients, mainly on macrophages. Objectives: The objectives of this study were to unravel the mechanisms underlying the effects of PRL and its receptor in RA. Methods: PRL levels in paired serum and synovial fluid (SF) were measured using immunofluorescent metric assay in 18 patients with active RA and 12 with PsA. PRLR expression was determined by RT-PCR in monocyte-derived macrophages from healthy donors polarized with granulocyte macrophage colony stimulating factor (GM-CSF), interferon gamma (IFN-y), interleukin 10 (IL-10), macrophage colony stimulating factor (M-CSF), and RA SF. Polarized monocyte-derived macrophages were stimulated with TNF (10 ng/ml) or LPS (1 ug/ml) plus PRL (25 ng/ml) for 24 hours. Proinflammatory cytokines were measured by ELISA. Results: PRL levels were comparable in serum and SF of patients with RA, respectively 10.3 (IQR 6.0-17.6) and 10.5 (IQR 7.5-17.5) ug/L. Similar PRL levels were found in PsA patients, respectively 14.5 (IQR 8.6-18.9) and 12.5 (7.5-17) ug/L. There was a correlation between the serum PRL levels and the levels in SF (r=0.6 p=0.000), suggesting systemic production of PRL. In IFN-y and IL-10 polarized monocyte-derived macrophages, PRLR mRNA expression was 100-200 times higher (p=0.042) compared to macrophages polarized in GM-CSF, M-CSF and RA SF. IFN-y differentiated macrophages displayed a dose-dependent increase in IL-6 production afer stimulation with TNFα plus PRL and LPS plus PRL (respectively p=0.042 and p=0.000, compared to TNFα or LPS alone). Similar results were found in IL-10 differentiated macrophages. Conclusions: Our observations in SF of inflammatory joint diseases suggest systemic rather than local production of PRL. In vitro, PRLR was expressed mainly by IFN-y and IL-10 polarized monocyte-derived macrophages. Upon stimulation of these macrophages with TNFα or LPS plus PRL, a dose-dependent increase of IL-6 production was observed. These results suggests that PRL may promote inflammation in RA and PsA via enhancing macrophage activation. References: Orbach et al. Ann N Y Acad Sci 2007 Ram et al. Rheumatology (Oxford) 2004 Seriolo et al. Ann N Y Acad Sci 2002 Figueroa et al. Rev Med Chil 1998 Disclosure of Interest: None Declared